The early Bronze age village on Tsoungiza hill - Pullen, Daniel Joseph, 1954- ‎. (Princeton, New Jersey)
xl, 1047 sayfa
Keywords: “While “corridor houses“ such as the House of the Tiles at Lerna have provoked widespread discussion about the origins of social stratification in Greece, few settlements of the Early Bronze Age (ca. 3100 to 2000 B.C.) have been thoroughly excavated. This important study integrates the presentation and analysis of the archaeological evidence from a single settlement that flourished on Tsoungiza Hill in the Nemea Valley from the Final Neolithic until the end of the Early Helladic period. The first section details the stratigraphy, architecture, deposits, and ceramics of each of the five major periods represented. The second section contains specialist reports on all aspects of material culture including figurines and ornaments, textiles and crafts, metal analyses, chipped and ground stone, and faunal and palaeobotanical remains“ -- Yayıncı.